Analisis Perbandingan Kualitas Air Laut Teluk Youtefa dan Yos Sudarso, Jayapura, Papua: Comparative Analysis of Seawater Quality of Youtefa and Yos Sudarso Bay, Jayapura, Papua - Hisyam, Muhammad; Sumardi, Sitti Rosnafi'an (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Youtefa Bay and Yos Sudarso Bay are bays located in Jayapura City. Yotefa Bay is a semi-closed coastal area because it is a small bay located in Yos Sudarso Bay. This condition makes the two bays have quite striking differences in sea dynamics. This is reinforced by the geographical location of the waters of Jayapura City which directly faces the Pacific Ocean which greatly affects the condition of the waters and the richness of its ecosystem. The richness of the coastal ecosystem in Youtefa Bay and Yos Sudarso Bay is closely related to the lives of the people living around the two bays. This study aims to analyze the comparison of seawater quality parameters in Youtefa Bay and Yos Sudarso Bay. The seawater quality data in question are temperature, salinity, and dissolved oxygen (DO) data. The study was conducted by taking temperature, salinity, and DO data in both bays at depths of 0 meters, 3 meters, and 5 meters. From these data, a comparative analysis will be carried out between sampling points to see the differences in values. In addition, an analysis of the average parameter differences between the two bays was also carried out. Based on the research results, each parameter has a fairly uniform distribution between each sampling point in each bay. The average temperature and DO values ​​in Youtefa Bay are higher than Yos Sudarso Bay because Yotefa Bay is a semi-enclosed water with many seagrass ecosystems in the bay. In addition, the average salinity value of Yos Sudarso Bay is higher than Youtefa Bay because Youtefa Bay receives direct input from the Pacific Ocean. Thus, based on the analysis, the temperature and salinity of the two bays show significant differences compared to the DO values ​​in the two bays.